EFEKTIVITAS PATCH TRANSDERMAL EKSTRAK SARANG BURUNG WALET (AERODRAMUS FUCIPHAGUS) TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM - Nurlina, Nurlina; Runjati, Runjati; Sunarjo, Lanny (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2024)
Perineal wounds due to childbirth can cause discomfort and infection. Transdermal patches of swallow's nest extract contain glycoproteins to stimulate wound healing. The study aimed to analyze the effectiveness of transdermal patches of swallow's nest extract on the healing of perineal wounds in postpartum mothers. The method used true experiment, pre-test, and post-test with control group design with randomized simple sampling technique. The sample was 34 postpartum mothers on the first day with grade II perineal wounds and suturing, normal delivery, aged 20-35 years, normal nutritional status, no diabetes, no infection, and hemoglobin levels of 11-15g/dl, and exclusion criteria were having complications during labor and postpartum. The sample consisted of 17 people in the intervention group who were given a 2.8g transdermal patch of swallow's nest extract by attaching it to the perineum and 17 people in the control group who were given 2.8 g of swallow's nest extract gel applied topically. Both groups were given intervention twice a day for 7 days and measurements were taken 4 times, on days 1, 3, 5, and 7. The measuring instrument used the REEDA. Analysis used Friedman, Mann Whitney, and Wilcoxon tests. The transdermal patch of bird's nest extract was faster in the wound healing process than the control group with an average REEDA score of 0.29 meaning good wound healing, while in the control group, it was 3.06 meaning poor wound healing with p-value<0.05. The transdermal patch of bird's nest extract is effective for healing perineal wounds in postpartum mothers.